2023
DOI: 10.3390/biom13040589
|View full text |Cite
|
Sign up to set email alerts
|

Genome and Genetic Engineering of the House Cricket (Acheta domesticus): A Resource for Sustainable Agriculture

Abstract: Background: The house cricket, Acheta domesticus, is one of the most farmed insects worldwide and the foundation of an emerging industry using insects as a sustainable food source. Edible insects present a promising alternative for protein production amid a plethora of reports on climate change and biodiversity loss largely driven by agriculture. As with other crops, genetic resources are needed to improve crickets for food and other applications. Methods: We present the first high quality annotated genome ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…BUSCO assessment of our annotation showed that a substantial portion of total gene content is likely not represented [odb10_insecta complete = 78.2% (single copy = 75.1%, duplicated = 3.1%), fragmented = 7.9%, missing = 13.9%; Fig. 3 ]; however, this was also the case (albeit less drastically) for our Helixer annotation of A. domesticus [odb10_insecta complete = 86.7% (single copy = 82.7%, duplicated = 4.0%), fragmented = 7.4%, missing = 5.9%; BUSCO complete in assembly = 94.8%; Dossey et al 2023 ] suggesting there may be biases in Helixer's premade invertebrate training data set, which is dominated by insects in the orders Diptera and Lepidoptera (details regarding Helixer training data sets can be found at https://uni-duesseldorf.sciebo.de/s/lQTB7HYISW71Wi0 ). Thus, the lower than expected recovery of single-copy orthologs may represent this bias rather than the quality of our assembly.…”
Section: Resultsmentioning
confidence: 73%
“…BUSCO assessment of our annotation showed that a substantial portion of total gene content is likely not represented [odb10_insecta complete = 78.2% (single copy = 75.1%, duplicated = 3.1%), fragmented = 7.9%, missing = 13.9%; Fig. 3 ]; however, this was also the case (albeit less drastically) for our Helixer annotation of A. domesticus [odb10_insecta complete = 86.7% (single copy = 82.7%, duplicated = 4.0%), fragmented = 7.4%, missing = 5.9%; BUSCO complete in assembly = 94.8%; Dossey et al 2023 ] suggesting there may be biases in Helixer's premade invertebrate training data set, which is dominated by insects in the orders Diptera and Lepidoptera (details regarding Helixer training data sets can be found at https://uni-duesseldorf.sciebo.de/s/lQTB7HYISW71Wi0 ). Thus, the lower than expected recovery of single-copy orthologs may represent this bias rather than the quality of our assembly.…”
Section: Resultsmentioning
confidence: 73%
“…It is geared towards small-scale studies requiring multiple strains or treatments, with the added requirement of having to fit within the confines of an average-sized molecular biology laboratory. This system also allows manipulation of WCR at different life stages, which is necessary when screening for genetic traits such as eye color or fluorescence, which are frequently used as markers when establishing transgenic or knock-out strains [ 21 , 30 , 31 ]. Importantly, it also addresses containment since reducing the risk of WCR escaping the confines of their rearing containers is of vital importance to both maintaining pure breeding strains and ensuring the insects never breach the confines of the laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of contiguousness, the G. longicercus assembly displays the third lowest N90, third highest L90 and the lowest number of total scaffolds. The A. domesticus genome 12 is currently the only publicly available cricket genome assembled at a chromosome level with the 11 chromosomes containing more than the 90% of the genome. After that genome, the genome assembly of G. bimaculatus and the herein presented assembly of G. longicercus are the most complete and contiguous cricket genomes.…”
Section: Methodsmentioning
confidence: 99%